Teaching with fandom: Promoting student subject engagement and critical reflection through fan fiction writing. - Roots, Jaime W. (Transformative Works & Cultures, 2025)
In a "Fairy Tales Through Pop Culture" literature course, I introduced the practice of internet fan fiction to engage students more fully in the course content. While this sort of creative writing project allows students to understand the transformative storytelling process, it is also a site of reflection and critique. As part of the process to help students understand the specific ways fairy tales can be adapted and what we can learn about the societies from which they originate, personal adaptation of fairy tales was an essential part of the course. Using a multiliteracies pedagogical approach, I present the strategies used to encourage student engagement, subject knowledge, and critical reflection on the subject matter, as well as student opinions and impressions of the project. While the use of this type of creative project can promote student engagement in courses, the methodology also promotes deep subject knowledge and critical reflection of the course materials covered.